Islamic Philanthropy: House of Zakat as a Funding and Capital Institution - Wahyu Hidayat (Al Qalam, 2023)
Every Islamic law that is revealed to the earth always has a maqasid sharia. Ibn Ashur defines maqasid sharia itself as the wisdom or value contained in the application of sharia. The purpose of stipulating zakat is an effort to reduce social inequality as well as to alleviate poverty. The problem is, so far zakat has not been very effective in poverty alleviation efforts. Mustahik still depends on the zakat issued by the rich every year. This paper aims to review zakat as an effort to alleviate poverty not only in the form of consumptive zakat but can act as an institution that encourages mustahik's productivity. This study uses a descriptive analysis method with a literature-based research model using literature related to productive zakat. The author found one zakat institution that was quite successful in processing zakat funds given to mustahik in the form of capital. This zakat institution is located in East Java. The capital given to the mustahik can be managed properly and make the mustahik change its status to muzakki. Mustahik is not only given capital in the form of money but also skills and supervision in managing the capital provided. Such Amil Zakat agency should be further developed in Indonesia as an effort to eradicate poverty more massively.